Pathways, Situations, and Factors Associated with Youth Violence in Educational Settings - Sripa, Kantita; Glubwila, Sorat; Thummaphan, Phonraphee (The Journal of Behavioral Science, 2021)
This qualitative research aimed to understand the pathways of youth violence in educational settings in Thailand, both on and off the school grounds, to study situation and patterns of youth violence, and to elaborate on factors associated with such violence. This study employed a life-history approach, in-depth interviews, focus groups, and observations at six schools. The key informants were 6 administrators, 30 teachers, 30 students, and 30 parents. The results found that there are two pathways of youth violence: one in which some youths are caught in a cycle of violence; and the other in which they have reached a turning point and were able to stop being violent, with support from adults, and by having clear goals for their future. As for the situation and patterns of youth violence, typically the children and youth in this study easily resorted to violence. Generally, male youngsters are more violent than females, and they tend to use violence outside of school. They think that carrying a weapon is normal behavior. They feel that the laws are not fair, which causes them to prefer taking revenge. There are six relevant dimensions of violent factors, including youths, family, friends, schools, the community, or society, and one’s culture, beliefs, and values. Each dimension can contribute to violent behavior and is related to the others. The findings have implications for youth behavior promotion and modification by involving various social groups, using socialization focused on appropriate psycho-social development, managing environment for stimulating positive behaviors, as well as cultivating good models, values and cultures for children and youth.